Recursos pedagógicos acessíveis ao aluno com surdocegueira por síndrome de Usher: um estudo de caso - Cambruzzi, Rita de Cássia Silveira (2013)
The objective of this work was to analyze the efficiency of visual adaptations in activities presented in the student with deafblindness with Usher syndrome and its impact on education. This research was developed in the city of Santa Catarina in a Basic Inclusive School where deaf education policy is performed in Elementary School in the first to ninth-grade and in High school. This is a case study for 12 year old preteen with deafblindness with Usher syndrome who studies in an Association of sensorineural deafness and acquired blindness as a result of Retinitis Pigmentosa. In the year 201, the student attended the 5th grade, in bilingual mode (only for deaf). In 6th grade (2012) in mixed class (with listeners). In the bilingual class the teacher, teaches in sign language as first language and the Portuguese, as second one. Already in the inclusive class the language used is Portuguese with the presence of an educational interpreter. It was used visual resources in the accessible instructional materials for the contents of the subjects. The bilingual students took advantage by the materials. Data collection consisted of the interview with the family, with the student, and the teacher. Also pre and post student s intervention with the application of functional vision instrument. Observations were conducted in different situations and in different spaces. The obtained results were analyzed qualitatively taking as a criterion the student s own performance analysis. The student makes use of sign language easily. He presented the first symptoms of Usher syndrome: dazzing in some situations which implied difficulty to adapt to bright; decreased peripheral vision and night blindness. In the process of perception of the difficulties he doesn t see as deafblind but like a deaf. During the collection of data it was observed signs of decrease in the peripheral vision, in the locomotion, and in the sign language when the colleague uses it in his side. The results suggest that the materials used in the classroom were mainly appropriate for the amplified material with 12 points to 20 or 20 points letters as gradual exposure in different sizes. The Times New Roman font was modified to the Arial font one and after to Verdana because the changes provided more suitable traits. The results indicate, therefore, that the accessible visual resources were used properly. However, there is no support of optical and non-optical resources by the institution on this new reality: the presence of the student with Usher syndrome, in the classroom, and his constitutional right is guaranteed.